A new organo-ruthenium substituted tungstotellurate: synthesis, structural characterization and catalytic properties. (16th September 2016) - Zheng, Da-Ming; Wang, Rui-Qiang; Du, Yu; Hou, Guang-Feng; Wu, Li-Xin; Bi, Li-Hua
Abstract : A novel organo-Ru supported tungstotellurate(iv ) has been synthesized and its catalytic activity was assessed towards the oxidation of n -tetradecane using air without any additives or solvents. Abstract : Reaction of [RuC6 H6 Cl2 ]2 with TeO2 and Na2 WO4 ·2H2 O in aqueous solution (pH 4.7) yielded a novel organo-ruthenium supported tungstotellurate polyanion, [Te2 W20 O70 (RuC6 H6 )2 ] 8− (Ru-1 ), which is composed of two [RuC6 H6 ] 2+ units linked to a [Te2 W20 O70 ] 12− fragment through Ru–O(W) bonds resulting in an assembly with idealized C 2h symmetry. Furthermore, the polyanionRu-1 was anchored on 3-aminopropyltriethoxysilane (apts)-modified SBA-15 to prepare new catalysts (SBA-15–apts–Ru-1 ) containing different amounts ofRu-1, which were characterized using powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), N2 -adsorption measurement and Fourier transform infrared reflectance (FT-IR) spectroscopy. Finally, the catalytic activity of SBA-15–apts–Ru-1 was evaluated for the aerobic oxidation of n -tetradecane using air as the oxidant in the absence of any additives or solvents. In addition, the optimum catalytic reaction conditions were also determined.